Social partnership in the field of education - as a transition to a new model of training competitive specialists - Karimovа Лязат (Рroblems of engineering and professional education, 2023)
The article deals with the issues of social partnership within the framework of the dual education system at the present stage of development of Kazakhstan. Features of dual educational programs.